2017
DOI: 10.1002/ppul.23771
|View full text |Cite
|
Sign up to set email alerts
|

Interrupter technique in infancy: Higher airway resistance and lower short‐term variability in preterm versus term infants

Abstract: Our results suggest that differences in airway mechanics between term and preterm infants can be assessed with the interrupter technique during early infancy. Before clinical application of Rint measurements in this age group, reasons underlying the variability of measurements should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…born before 37 gestational weeks), quantitative variability of tidal volume and endtidal expiratory CO 2 is significantly lower in patients with chronic lung disease of infancy than in patients without supplementary oxygen or CPAP [43]. At the postmenstrual age of 42-50 weeks, the quantitative variability of airway resistance is significantly higher in term infants than in preterm infants [44]. In preterm born infants, lower quantitative variability of tidal volume at a postmenstrual age of 44 weeks is an important predictor of re-hospitalization due to respiratory disease in infancy [45].…”
Section: Lung Prematuritymentioning
confidence: 96%
“…born before 37 gestational weeks), quantitative variability of tidal volume and endtidal expiratory CO 2 is significantly lower in patients with chronic lung disease of infancy than in patients without supplementary oxygen or CPAP [43]. At the postmenstrual age of 42-50 weeks, the quantitative variability of airway resistance is significantly higher in term infants than in preterm infants [44]. In preterm born infants, lower quantitative variability of tidal volume at a postmenstrual age of 44 weeks is an important predictor of re-hospitalization due to respiratory disease in infancy [45].…”
Section: Lung Prematuritymentioning
confidence: 96%
“…full term and preterm infants ranging from 42 to 50 weeks postmenstrual age. 36 They found that Rint was elevated in premature infants, but there was high intra-measurement variability. The latter finding may limit the clinical application of Rint in preterm infants.…”
Section: Usemann Et Al Measured Interrupter Resistance (Rint) In Unsementioning
confidence: 99%
“…Pulmonary function testing in infants remains challenging. Usemann et al measured interrupter resistance (Rint) in unsedated full term and preterm infants ranging from 42 to 50 weeks postmenstrual age . They found that Rint was elevated in premature infants, but there was high intra‐measurement variability.…”
Section: Introductionmentioning
confidence: 99%